Multidisciplinary model of sexually transmitted infection prevention in the group of injecting drug users - T. V. Krasnoselskikh; A. V. Shaboltas; R. V. Skochilov; G. E. Uraeva (Vestnik Dermatologii i Venerologii, 2017)
The article summarizes the experience in developing, implementing and effectiveness evaluating of the sexually transmitted infection prevention program in the subpopulation of injecting drug users in St. Petersburg, Russia. The preventive intervention was aimed to correct behaviors leading to infection and was based on a multidisciplinary patient-centered approach. Long-term medical, social and psychological support of injecting drug users, combined with the group training sessions based on the peer-to-peer model has allowed to reduce their injecting and sexual risk, as well as to decrease the HIV infection incidence in the intervention group 1.84 times against the control group.